2021
DOI: 10.1029/2021jd035440
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric NO2 and O3 Response to COVID‐19 Lockdown Restrictions at the National and Urban Scales in Germany

Abstract: This study estimates the influence of anthropogenic emission reductions on nitrogen dioxide (normalNnormalO2) and ozone (O3) concentration changes in Germany during the COVID‐19 pandemic period using in‐situ surface and Sentinel‐5 Precursor TROPOspheric Monitoring Instrument (TROPOMI) satellite column measurements and GEOS‐Chem model simulations. We show that reductions in anthropogenic emissions in eight German metropolitan areas reduced mean in‐situ (& column) normalNnormalO2 concentrations by 23 % (& 16 %) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 109 publications
(175 reference statements)
1
4
0
Order By: Relevance
“…While, O 3 was significantly (p = 0.02) higher in 2020 than that in 2010–2019, which indicated that O 3 pollution was also affected by those measures. These phenomena were also comparable with previous studies ( Balamurugan et al, 2021 ; Cazorla et al, 2021 ; Sicard et al, 2020 ).
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…While, O 3 was significantly (p = 0.02) higher in 2020 than that in 2010–2019, which indicated that O 3 pollution was also affected by those measures. These phenomena were also comparable with previous studies ( Balamurugan et al, 2021 ; Cazorla et al, 2021 ; Sicard et al, 2020 ).
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…This performance improvement could be attributed to the pronounced seasonal cycle of ozone and weekday-weekend differences. The ozone reaches its maximum in summer and minimum in winter, and due to being in a NO saturated regime, weekend ozone levels are higher than the weekdays 13 . The ML algorithm trained solely with CAMS (“ML_cams”) or in-situ precursors (“ML_insitu”) show poor performance in all terms when compared to ML algorithm trained with the meteorology category alone (“ML_met_ds”) (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, VOC emissions from volatile chemical products such as cleaning agents and personal care products are becoming more significant 12 . Recent ozone enhancements in urban areas during the COVID-19 lockdown period demonstrate the NO saturated regime’s ozone production chemistry 13 , 14 . Chemical transport models (CTM) are widely used to study the ozone variability 15 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing capability of satellite monitoring from space has enabled studies to better characterize pollution patterns, such as analyzing the responses of trace gases to either anthropogenic or biogenic sources (Balamurugan et al., 2021; Pu et al., 2022; R. Zhang et al., 2020) and investigating regional emission trends (DiMaria et al., 2023; Krotkov et al., 2016; J. Li & Wang, 2019). The uncertainties of satellite products consist of both systematic and random components.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with surface measurements, which are limited in spatiotemporal coverages, satellite observations of tropospheric vertical column densities (TVCDs) can provide continuous data sets with a broad spatial range. The Ozone Monitoring Instrument (OMI) and the TROPOspheric Monitoring Instrument (TROPOMI) have provided continuous measurements of NO 2 and HCHO to advance our understanding of the related atmospheric chemical processes (Balamurugan et al., 2021; Lamsal et al., 2010; D. Li et al., 2021; J. Li & Wang, 2019; H. J. R. Wang et al., 2020; Zeng et al., 2008; Y. Zhang et al., 2018). OMI aboard NASA's Aura satellite has been in orbit since 2004.…”
Section: Introductionmentioning
confidence: 99%